2020
DOI: 10.1002/nau.24368
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with urinary incontinence in a community sample of young nulligravid women

Abstract: Aims The aim of this study is to identify factors associated with urinary incontinence (UI) in a community sample of young nulligravid women. Methods This was a secondary analysis from a cross‐sectional survey‐based study of cisgender women aged 18 to 25 years recruited through a national registry of research volunteers. Participants completed validated questionnaires assessing toileting behaviors, lower urinary tract symptoms (LUTS), and bowel symptoms. Women were excluded from analysis if currently pregnant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
3
6
0
4
Order By: Relevance
“…These behaviors could be a response to limited bathroom time, which is anecdotally not uncommon in physicians, but may be more common in trainees. The study findings align with prior studies demonstrating a pronounced association between LUTS and abnormal toileting behaviors in full-time working women in the United States 21 as well as in nulligravid women in the United States, 33 and among other advanced practice health care providers 22 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These behaviors could be a response to limited bathroom time, which is anecdotally not uncommon in physicians, but may be more common in trainees. The study findings align with prior studies demonstrating a pronounced association between LUTS and abnormal toileting behaviors in full-time working women in the United States 21 as well as in nulligravid women in the United States, 33 and among other advanced practice health care providers 22 …”
Section: Discussionsupporting
confidence: 90%
“…These behaviors could be a response to limited bathroom time, which is anecdotally not uncommon in physicians, but may be more common in trainees. The study findings align with prior studies demonstrating a pronounced association between LUTS and abnormal toileting behaviors in full-time working women in the United States 21 as well as in nulligravid women in the United States, 33 and among other advanced practice health care providers 22 Finally, most participants reported worrying about the cleanliness of toilets, which could explain altered toileting behavior in public places compared with home. These altered voiding positions were not significantly associated with LUTS in this study.…”
Section: Discussionsupporting
confidence: 89%
“…First birth before age 32 make decrease the risk of urinary incontinence after delivery.Urinary incontinence (UI), is one of the problems during pregnancy and the postnatal period, with a prevalence ranging from 5 to 70% 1,2 . It is not only an organic lesion, but also causes psychological problems such as depression and reduced self-esteem 3,4 , which can seriously affect a woman's quality of life 5 .Recent evidence suggests that advanced maternal age at pregnancy, timing of delivery, pregnancy, obstetric trauma and mode of delivery, infant birthweight, infant head circumference, obesity and ageing, and bladder neck hypermobility are the risk factors for UI [6][7][8] . Age at first birth is associated with mortality 9 , BMI 10 , and cancer 11 .…”
mentioning
confidence: 99%
“…Recent evidence suggests that advanced maternal age at pregnancy, timing of delivery, pregnancy, obstetric trauma and mode of delivery, infant birthweight, infant head circumference, obesity and ageing, and bladder neck hypermobility are the risk factors for UI [6][7][8] . Age at first birth is associated with mortality 9 , BMI 10 , and cancer 11 .…”
mentioning
confidence: 99%
“…19,25 Recent research with young women reported an association between delayed voiding and urinary incontinence. 26 Participants described family caregiving responsibilities including assisting with toileting and monitoring toileting behaviors. They described neglecting their health while attending to family members.…”
Section: Caregiving For Family Members' Bladder Needsmentioning
confidence: 99%